The Effect of Hidden Words Game on the EFL Students' Vocabulary Mastery - Intan Panca Mirta; Fitri Budi Suryani; Nuraeningsih Nuraeningsih (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2021)
Teaching vocabulary to EFL students in this era can be a challenging task regarding their characteristic as the millenial generation. That’s why, the proper choice of media to teach is needed that will enable EFL students to learn vocabulary effectively. This study aims to find out if hidden words game application can increase English vocabulary mastery of the EFL students. The design of the research was quasi experimental using a single group model of pre-test and post-test. The population of the study was the seventh grade students of SMPN 2 Kudus with class D as the sample consisting of 32 students. The instrument of the research was multiple choice test. The research finding revealed that hidden words game application can increase the English vocabulary mastery of seventh graders.